Case Report: An Unusual Case of Acute Lower Limb Ischemia as Precursor of the Asherson's Syndrome - Pasqui, Edoardo; Camarri, Silvia; de Donato, Gianmarco; Gonnelli, Stefano; Palasciano, Giancarlo; Gennari, Luigi (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Asherson's Syndrome, also defined as Catastrophic Antiphospholipid Syndrome (CAPS), represents the most severe manifestation of Antiphospholipid Antibody Syndrome. Rarely, the first CAPS diagnosis is based on macro-thrombotic event as acute limb ischemia. Case Presentation: We present a case of a 65-year-old woman admitted with an acute lower limb arterial ischemia with a complete occlusion of all the three tibial vessels. Three endovascular recanalization procedures were performed contemporary to 48 h intraarterial thrombolysis administration. The patency of tibial arteries was restored with a near-complete absence of digital arteries and microvessel perfusion of the foot. In the following days, an aggressive foot gangrene was established, leading to a major lower-limb amputation. Due to the general clinical status worsening and aggressiveness of ischemic condition, further investigations were performed leading to the diagnosis of an aggressive Asherson's Syndrome that was also complicated by a severe heparin-induced thrombocytopenia. Medical management with a high dose of intravenous steroids and nine sessions of plasma exchange led to a clinical condition stabilization. Conclusion: In our case, the presence of a “sine causa” acute arterial occlusion of a large vessel represented the first manifestation of an aggressive form of Asherson's Syndrome that could represent a fatal disease. Due to the extreme variety of manifestations, early clinical suspicion, diagnosis, and multidisciplinary management are essential to limit the life-threatening consequences of patients.